Preparation for ISO 9001 implementation : Process identification - Lebeda, Petr; Martínez, Felipe; Vinš, Marek; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This bachelor's thesis aims to determine the main processes of a selected wholesale company, with the purpose of helping it with the preparation for the ISO 9001:2015. The theoretical part focuses on describing the role and operations of the wholesale industry, along with describing the ISO 9001:2015, its requirements, and challenges. The process identification tools, described in the methodological part, are used to determine the company’s processes. The practical part of the thesis focuses on a wholesaler of cleaning supplies. In the research, the author first introduces the context of the company using Porter’s five forces and then identifies a list of the company’s main processes. Processes are further assessed by Pareto analysis, based on which are selected three for more detailed identification, done by applying Process identification, SIPOC, and Flowchart. Additionally, improvements in the selected processes are offered, by identifying waste, and using PDCA cycle are proposed changes to help enhance and standardise the selected processes.
Vedoucí práce: Felipe Martínez
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses